In Situ Synthesis of MnMgFe-LDH on Biochar for Electrochemical Detection and Removal of Cd2+ in Aqueous Solution - Yu, Yongfang; Yang, Wenting; Wang, Haocheng; Huang, Guoqin (Molecules (Basel, Switzerland), 2022)
Herein, MnMgFe-layered double hydroxides/biochar (MnMgFe-LDHs/BC) composite was fabricated by immobilizing MnMgFe-LDHs on BC via the coprecipitation method, which was employed as an effective material for the detection and removal of Cd2+ from aqueous media. A lamellar structure of MnMgFe-LDHs with abundant surface-hydroxyl groups and various interlayer anions inside present a greater chance of trapping Cd2+. Meanwhile, the conductive BC with a porous structure provides numerous channels for the adsorption of Cd2+. Using the MnMgFe-LDHs/BC-based sensor, Cd2+ can be detected with a low limit of detection down to 0.03 ng/L. The feasibility of detecting Cd2+ in paddy water was also carried out, with satisfactory recoveries ranging from 97.3 to 102.3%. In addition, the MnMgFe-LDHs/BC material as an adsorbent was applied to remove Cd2+ from water with adsorption capacity of 118 mg/g, and the removal efficiency can reach 91%. These results suggest that the as-prepared MnMgFe-LDHs/BC can serve as a favorable platform for efficient determination and removal of Cd2+ in water.